213 EARLY IDENTIFICATION AND NUTRITION INTERVENTION OF FRAIL ADULTS AT RISK OF MALNUTRITION BY AN EMERGENCY DEPARTMENT FRAILTY INTERVENTION TEAM (FIT). (25th October 2022) - Pender, C; Magner, S; Carrabine, N; Byrne, C; Riches, R; Mitchell, M; Buckley, B; Carey, S; Harrington, G; Caheny, CO; Laguna, R
Abstract: Background: Frailty is a nutrition related condition which is potentially reversible if modifiable risk factors including malnutrition are identified at an early stage. National guidance recommends early identification of risk of malnutrition and provision of timely, appropriate oral nutritional support. Over ⅓ of older adults presenting to the Emergency Department (ED) are malnourished/at risk of malnutrition. This study evaluates the early identification and nutrition intervention of frail adults at risk of malnutrition by FIT. Methods: A retrospective study of frail patients presenting to a level 4 hospital ED over three months was performed. Each patient had a Comprehensive Geriatric Assessment performed. A referral to Dietetics was indicated by: Malnutrition Screening Tool (MST) score ≥2, dysphagia, grade ≥2 pressure ulcer or already prescribed oral nutritional supplements (ONS). Data was collected from a Hospital Clinical System using Excel®. The data recorded included: Clinical Frailty Score (CFS), referral reason, 4AT and admit/discharge location. Results: 117 frail patients were referred to Dietetics by FIT. The median CFS was 5 (mildly/moderately frail) with an IQR of 1. 43%(n=50) had 4AT=0. 75%(n=88) had MST ≥2 identifying risk of malnutrition 13.6%(n=16) were already prescribed ONS 9.4%(n=11) had dysphagia 6.8%(n=8) had a grade ≥2 pressure ulcer Nutrition support intervention was provided by the Dietitian to 100% (n=117) within 24 hours of referral. 27% (n=32) were discharged from ED and 72% (n=85) were admitted. Conclusion: FIT have successfully implemented recommendations from the National Clinical Guideline No.22. Early dietetic intervention in ED, for those admitted and discharged, may prevent the onset/progression of malnutrition in frail patients.